Factors Influencing Fast Food Restaurant Generation Y Customers’ Retention in Selangor Malaysia - Chean, Kok Soong (2016)
The purpose of thesis is to investigate customers’ retention Generation Y towards fast food restaurants in Selangor, Malaysia. In this thesis, data was collected quantitatively where convenience sampling method was specially obtained through questionnaires on 512 participants who dine in fast food restaurants, Selangor, Malaysia. Multiple Regression and Pearson Correlation was applied to analyse three factors, which are food quality, service quality and restaurant environment that may influence the positive customers’ experience. The results identify that the customers have passion to revisiting fast food restaurants due to the food quality, service quality and restaurant environment offered by them. This study offers the fast food restaurants to increase the understanding on customer retention among their actual and potential customers. All result of this thesis was used Statistical Package for the Social Sciences 22.